COVID 19: AUTOMATIC DISCHARGE OF BANKRUPTCY IN MALAYSIA FROM THE ISLAMIC POINT OF VIEW - Rehah binti Ismail (International Journal of Accounting, Finance and Business, 2021)
Indeed, the Covid-19 virus is feared by the world community. In China the virus emerged. This Covid-19 has caused fatalities globally. The Governments across the state have taken measures to resolve the issue of the Covid-19 epidemic by formulating a Movement Control Order strategy. The pandemic Covid-19 is impacting corporations and the global economy. Many private and government employees have lost their jobs because of the unstable economy. The individual who has financial problem will borrow the monies from the financial institution. The deteriorating economy caused the individual to be unable to pay the debt and eventually decided to voluntarily bankrupt himself or the financial institution that bankrupt the individual. The business sector is deteriorating and companies are voluntarily winding up the company. In addition, the bank had to wind up the company to recover the money that had been lent to the company. This article explores the view of automatic discharge of bankruptcy in Malaysia from the point of view of Islamic proposals based on Al-Quran, al-hadith, ijmak ulamak and qiyas. Malaysia adopted the Bankruptcy Law inherited from Roman Law in the 451 century. Islamic view on bankruptcy is evaluated from the point of view of Al-Quran, ahadith, jjmak ulamak and qiyas.